Perioperative Anesthetic Management of Intrabuccal Fibroma Excision in a Patient with Marfan Syndrome: A Case Report - Reza Rahardian; Hermin Prihartini; Rudi Prihatno (Bali Journal of Anesthesiology, 2025)
Marfan syndrome is a connective tissue disorder with multisystemic involvement, particularly affecting the cardiovascular, musculoskeletal, and respiratory systems. Anesthetic management in these patients requires careful planning to avoid life-threatening complications such as aortic dissection, arrhythmias, and airway trauma. This report describes the perioperative management of a patient with Marfan syndrome undergoing excision of an intrabuccal fibroma. A 23-year-old female with a known diagnosis of Marfan syndrome presented with a longstanding right buccal swelling, recently associated with intermittent dental pain. Her medical history included mitral valve prolapse with mild regurgitation, asthma, and prior scoliosis surgery. Preoperative echocardiography revealed grade II diastolic dysfunction and anterior mitral leaflet prolapse. Pulmonary examination was unremarkable. The patient was optimized preoperatively in collaboration with cardiology and pulmonology teams. General anesthesia with endotracheal intubation was chosen for the intraoral procedure. Induction agents included midazolam, fentanyl, propofol, and rocuronium, with maintenance using sevoflurane. Intravenous lidocaine was administered to attenuate airway reflexes. The intraoperative course was uneventful, with stable hemodynamics and minimal blood loss. The patient was extubated safely and discharged home in stable condition after two days. This case highlights the importance of individualized anesthetic planning in patients with Marfan syndrome, emphasizing cardiovascular protection, careful airway assessment, and multidisciplinary optimization. Even for minor surgical procedures, such patients require a thorough preoperative evaluation and intraoperative vigilance to minimize perioperative risk.